Non-Fullerene Organic Electron-Transporting Materials for Perovskite Solar Cells - Jung, Su Kyo; Lee, David S.; Ann, Myung Hyun; Im, Sang Hyuk; Kim, Jong H.; Kwon, O. Pil (ChemSusChem, 2018)
Invited for this month′s cover is the collaborative team of the groups of O-Pil Kwon and Jong H. Kim at Ajou University and Sang Hyuk Im at Korea University. The image shows non-fullerene organic electron transporting materials for perovskite solar cells. The Concept itself is available at 10.1002/cssc.201801908.